First Contact ‐ Take 2: Using XR technology as a bridge between Māori, Pākehā and people from other cultures in Aotearoa, New Zealand. Issue 1 (1st June 2021) - Gunn, Mairi; Billinghurst, Mark; Bai, Huidong; Sasikumar, Prasanth
The art installation common/room explores human‐digital‐human encounter across cultural differences. It comprises a suite of extended reality (XR) experiences that use technology as a bridge to help support human connections with a view to overcoming intercultural discomfort (racism). The installations are exhibited as an informal dining room, where each table hosts a distinct experience designed to bring people together in a playful yet meaningful way. Each experience uses different technologies, including 360° 3D virtual reality (VR) in a headset (common/place), 180° 3D projection (Common Sense) and augmented reality (AR) (Come to the Table! and First Contact ‐ Take 2). This article focuses on the latter, First Contact ‐ Take 2, in which visitors are invited to sit at a dining table, wear an AR head-mounted display and encounter a recorded volumetric representation of an Indigenous Māori woman seated opposite them. She speaks directly to the visitor out of a culture that has refined collective endeavour and relational psychology over millennia. The contextual and methodological framework for this research is international commons scholarship and practice that sits within a set of relationships outlined by the Mātike Mai Report on constitutional transformation for Aotearoa, New Zealand. The goal is to practise and build new relationships between Māori and Tauiwi, including Pākehā.